(untitled) (International Journal of Engineering Management Science, 2022)
High voltage gain DC-DC converters are required in many industrial applications such as PV and fuel cell energy systems, high intensity discharge lamp(HID), DC back-up energy systems and electric vehicles. This paper presents a novel input-parallel output-series boost converter with dual coupled-inductors and a voltage multiplier module. On the one hand, the primary windings of two coupled-inductors are connected in parallel to share the input current and reduce the current ripple at the input. On the other hand, the proposed converter inherits the merits of interleaved series-connected output capacitors for high voltage gain, low output voltage ripple and low switch voltage stress. On the other hand, the proposed converter inherits the merits of interleaved series-connected output capacitors for high voltage gain, low output voltage ripple, and low switch voltage stress. Moreover, the secondary sides of two coupled inductors are connected in series to a regenerative capacitor by a diode for extending the voltage gain and balancing the primary-parallel currents. In addition, the active switches are turned on at zero current and the reverse recovery problem of diodes is alleviated by